The unquiet dead : a novel - Murphy, Stacie (Pegasus Crime, an imprint of Pegasus Books, 2022)
"The new Gilded Age mystery featuring the uniquely talented Amelia Matthew--who has the ability to communicate with the dead--as she uses her special talents to solve the murder of a young girl whose death has scandalized New York City. Three months after her harrowing experience on Blackwell's Island, Amelia is doing her best to come to terms with her new abilities to commune with the spirit world. The last thing she wants to do is hunt for another killer through the streets of Gilded Age New York. But when she and Jonas discover the body--and spirit--of a young girl whose kidnapping has electrified the city, Amelia's resolve wavers. It breaks entirely when a fifteen-year old boy--the son of one of the club's black waiters and his Irish immigrant wife--is accused of the crime. With the city in an uproar and an ambitious reporter watching their every move, Amelia and her brother Jonas set out to discover the truth. And they have to do it quickly: in five days, the boy will be transferred to the brutal Sing Sing prison to await trial. For such a notorious suspect, it's as good as a death sentence. But all the evidence seems to point to the boy's guilt. Worse, the murdered child wasn't the first: there have been at least five other victims. As tensions rise throughout the city, the boy's family is subjected to an escalating campaign of violence and intimidation, culminating in the firebombing of their home. In the chaotic aftermath, Amelia taps into her special talents to search for the clues that will unmask the killer." -- Jacket flap.